Properties of fuzzy absolute value on R and Properties Finite Dimensional Fuzzy Normed Space - Kider, Jehad R.; Ali, Ahmed H. (Iraqi Journal of Science, 2018)
The first aim in this paper is to introduce the definition of fuzzy absolute value on the vector space of all real numbers then basic properties of this space are investigated. The second aim is to prove some properties that finite dimensional fuzzy normed space have.